Sustainability and Energy Politics - Curran, Giorel. author. aut Link
IX, 235 p.
Keywords: The author explores the fraught politics of energy transitions in an age of climate change. She does so through an ecological modernisation and corporate social responsibility lens which she contends shapes and underpins sustainability today. Case studies cover climate policy, unconventional gas and renewable energy.